Hubungan Lama Kerja Dan Sikap Kerja BerdiriDengan Keluhan Nyeri Punggung BawahPada Pekerja Batik Cap Di KampungBatik Laweyan Surakarta - Naza, Avyda Aulia; , Heru Subaris Kasjono, SKM., M. Kes; , Dwi Astuti, SKM., M. Kes (2016)
Textile industry especially in batik stamp was production process did by stand up. This process would get an ergonomi problem, like a low back pain. It was cause by stretching muscles, more activities and the manner of work which was not naturally likes we were standing up. The purpose if this research was to know the relationship between the length of working and the manner of work which felt pain low back pain according to employee of batik stamp in Kampung Batik Laweyan Surakarta. The design of this research was analytic survey which was the cross sectional study as the research plan. The population of this research were 33 employee of batik stamp. The sample of this research exhaustive sampling which had 33 employee. Instruments of this research was RULA method and NBM to measure the manner of working and questionnaire. The relationship analysis did by statistical an analysis of chi square. The result of a length time batik stamps employee in Kampung Batik Laweyan Industry Surakarta almost did a work for about 33-40 hour in a week. The attitude of batik stamps employee in Kampung Batik Laweyan Industry which was count by NBM method intermediate risk mostly and the attitude of work appear RULA method high risk mostly. An analysis result: 1)There was a significant relevant of a length work to low back pain on batik stamps employee in Kampung Batik Laweyan Industry Surakarta (p < 0,05). 2) There was a significant relevant of working attitude appear NBM method to low back pain of batik stamps employee in Kampung Batik Laweyan Industry Surakarta (p < 0,05). 3) There was a significant relevant of working attitude appear RULA method to low back pain of batik stamps employee in Kampung Batik Laweyan Industry Surakarta (p < 0,05).